2003
DOI: 10.1111/j.0014-3820.2003.tb00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Selection on Arrival Times in Sticklebacks: Why Small Males Arrive First

Abstract: Studies on arrival time to breeding areas show that high‐quality males usually arrive first and gain the highest reproductive success. This is generally assumed to be due to phenotype‐dependent costs and benefits of early arrival. We show that the opposite arrival order can occur, probably due to selection on poor‐quality males to increase their chances of reproduction. In a fish species, the threespine stickleback, Gasterosteus aculeatus, small males arrived before larger males at the breeding grounds. Early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 81 publications
(101 reference statements)
3
37
0
Order By: Relevance
“…In some areas, herring spawned in discrete waves such that the oldest females in the stock descending to age 4 years spawned in the first wave, while small 4-year olds and age 3 years first-time spawners in the second wave, about 16 days later (Ware and Tanasichuk 1989). The behaviour of older members of a stock may also be important where males are territorial as larger fish are likely to displace younger fish from premium spawning sites (Ridgway et al 1991;Candolin and Voigt 2003). There also seems to be a body size/age component to arrival on spawning grounds such that larger, older, experienced spawners tend to enter sites ahead of first-time spawners and this demographic element is likely to be embodied with environmental driven variation (Ridgway et al 1991;Trippel et al, 1997;Lawson and Rose 2000;Vandeperre and Methven 2007).…”
Section: Fishery-induced Changes In Spawning Time P J Wright and E A mentioning
confidence: 99%
“…In some areas, herring spawned in discrete waves such that the oldest females in the stock descending to age 4 years spawned in the first wave, while small 4-year olds and age 3 years first-time spawners in the second wave, about 16 days later (Ware and Tanasichuk 1989). The behaviour of older members of a stock may also be important where males are territorial as larger fish are likely to displace younger fish from premium spawning sites (Ridgway et al 1991;Candolin and Voigt 2003). There also seems to be a body size/age component to arrival on spawning grounds such that larger, older, experienced spawners tend to enter sites ahead of first-time spawners and this demographic element is likely to be embodied with environmental driven variation (Ridgway et al 1991;Trippel et al, 1997;Lawson and Rose 2000;Vandeperre and Methven 2007).…”
Section: Fishery-induced Changes In Spawning Time P J Wright and E A mentioning
confidence: 99%
“…A "cascading" race to arrive early (Kokko 1999) would then not be observed. Such a strategy has indeed been described for territorial male sticklebacks Gasterosteus aculeatus; large males were found to arrive later than small males because they were able to take over territories on arrival (Candolin and Voigt 2003).…”
Section: Discussionmentioning
confidence: 73%
“…The pool experiment showed that in a group of both nesting and non-nesting males, nesting males performed most sneak fertilizations, with attractive males with a high courtship success sneaking the most, but decreasing sneaking in dense vegetation where the success rate of sneak attempts was low. The aquarium experiment revealed that males were more willing to risk their current reproductive success for a sneak opportunity when the perceived value of current offspring was low, but that risk taking increased with male body size, which presumably correlated with future reproductive opportunities [33]. These results suggest that males adjust sneaking to its context-dependent costs and benefits.…”
Section: Discussionmentioning
confidence: 89%
“…The third possibility, that non-nesting males refrained from sneaking in favor of future nesting opportunities is also plausible, as the intensity of competition for nesting sites varies spatially and temporally under natural conditions [33]. The competitive ability and attractiveness of males could change over the season, particularly as they show indeterminate growth [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation